Perceptions About The Effect Of Virtual Education During Covid 19 On Learner Engagement And Motivation In Iraq (Journal of the College of Basic Education, 2024)
This study aims to explore the Perceptions about the Effect of Virtual Education during Covid 19 on Learner Engagement and Motivation in Iraq. In order to investigate how virtual education affects learners' motivation and engagement, a qualitative research approach was selected for this study. Given that online education is a complicated phenomena that negatively impacts students' performance (Hanifa, 2018), a qualitative study approach is appropriate to highlight its intricacy. In qualitative research, the researcher interviews EFL Iraqi Students to investigate the effects of virtual education on learner's engagement and motivation. The researcher presented interview questions to 20 participants. the virtual education during Covid 19 on learner engagement is negative as students explained that they are not fully understanding the lectures and instructors do not use activities during the online class which makes the lecture boring and not interesting. According to second research question, students' perceptions about the effect of virtual education during Covid 19 on motivation is negative. Students are not motivated during the lecture as the online lectures lack many factors such as the attendance of students, participation during the lecture, and preparation.